2007
DOI: 10.1111/j.1468-2982.2007.01401.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Triptans Use: A Study Based on the Records of a Community Pharmaceutical Department

Abstract: Studies performed in selected populations show that the use of triptans for migraine is low. Our study was aimed at establishing patterns of triptan utilization in a large community using the drug prescription database of a regional Health Authority in Italy. In a population of 224,065 residents, 0.55% received at least one prescription of triptans in 1 year: 77.9% were female and 22.1% male. Oral dosage forms accounted for 94% of prescriptions. About 60% of patients received a single prescription (containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 17 publications
(22 reference statements)
6
36
1
1
Order By: Relevance
“…We found that the percentage of patients not persistent past their index triptan was nearly 54%; as compared to the 39% single-time use of triptans among those not on prophylactics found within a similar US-based population in the Etemad et al study (17). Our triptan persistency results are closer to the singletime triptan utilization results in ex-US populations, which range from 42% to 56% (11)(12)(13)15), and also do not differentiate between those on concomitant prophylactic therapies. Furthermore, patients in this study population are representative of US-based triptan users and migraineurs in general with respect to gender, age and comorbid disorders.…”
Section: Discussionsupporting
confidence: 72%
“…We found that the percentage of patients not persistent past their index triptan was nearly 54%; as compared to the 39% single-time use of triptans among those not on prophylactics found within a similar US-based population in the Etemad et al study (17). Our triptan persistency results are closer to the singletime triptan utilization results in ex-US populations, which range from 42% to 56% (11)(12)(13)15), and also do not differentiate between those on concomitant prophylactic therapies. Furthermore, patients in this study population are representative of US-based triptan users and migraineurs in general with respect to gender, age and comorbid disorders.…”
Section: Discussionsupporting
confidence: 72%
“…Other studies describing the percentage of triptan users, in periods when more triptans are available, are reported in Table 4 [5, 6, 815]. The prevalence of triptan users in a year period was 0.55–1.4%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Utilization patterns of specific anti-migraine drugs in community patients and the experiences of patients with these drugs in real life setting have been studied less extensively. Recently we have performed a study evaluating triptans utilization in a health authority in Tuscany covering about 225,000 residents [4, 5]. We have extended this study to establish the patterns of use of triptans in a large sample of Italian population [6] and review other studies on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…In this controlled trial early administration of the triptan produced significantly greater symptomatic relief compared with treatment given when the pain had become more severe 16 . Thus, there appears to be a certain lack of association between current best-evidence relating to the diagnosis and management of migraine, and what occurs in the 'real world' 17 .…”
Section: Introductionmentioning
confidence: 98%